IDENTIFIKASI KESALAHAN DALAM MAKALAH MAHASISWA DITINJAU DARI KEMAMPUAN KOMUNIKASI MATEMATIS - Fitrianto Eko Subekti; Reni Untarti (AlphaMath : Journal of Mathematics Education, 2016)
ABSTRACT: This research is aimed to identify errors on working paper which is written by the students observed from mathematic communicative competence. This research is included descriptive research. The subjects of this research are the students of mathematic department that get remedial in lesson matematika sekolah 4. There are nineteen students. The data is taken from the working paper which is written by the students. The sample is taken using purposive sampling technique. The working paper that is used include: (1) statistic; (2) exponents and logarithms; (3) sequence and series. Based on the research can be concluded that: errors on working paper which is written by the students observed from mathematic communicative competence are: (1) inconsistencies and inaccuracies in using mathematic symbol; (2) unability in describing inequality solution; and (3) less capable in showing tables and informative issues. KEY WORDS: error identification, mathematic communicative competence